PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA PABRIK TAHU DUA PUTRI PANJI SITUBONDO - Sarwono, Aji; Ediyanto, Ediyanto; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
The importance of marketing in the business world lies in its role as a bridge between companies and customers . One of the crucial aspects of marketing is the relationship between product quality and customer satisfaction . When product quality meets consumer expectations , this results in satisfaction , which in turn can form customer loyalty . This loyalty then drives positive interactions that serve to attract new customers . This study aimed to analyze and test the effect of product quality and trust on customer satisfaction with purchasing decisions as an intervening variable at Dua Putri Tofu Factory , Panji , Situbondo . The population in this study were consumers of the Dua Putri Tofu Factory . The sampling technique was determined by simple random sampling . Data analysis and hypothesis testing in this study using the Structure Equation Model - Partial Least Square ( PLS - SEM ). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that product quality has a significant effect on purchasing decisions , trust has a significant effect on purchasing decisions , product quality has a positive but insignificant effect on customer satisfaction , trust has a significant effect on customer satisfaction , purchasing decisions have a significant effect on customer satisfaction , product quality has a positive but insignificant effect on customer satisfaction through purchasing decisions , trust has a positive but insignificant effect on customer satisfaction : through purchasing decisions.